Testing factorial validity of motivational constructs using confirmatory factor analysis - Awang Hashim, Rosna (Universiti Utara Malaysia, 2000)
The present study examines the validity of the newly translated Malay version of the "State Self-assessment" and "Trait Self-assessment" instruments. These instruments are each composed of three constructs that are considered integral to the social cognitive theories of motivation: self-eficacy, efort, and worry. Data were collected from 360 college undergraduates at Universiti Utara Malaysia. A confirmatory factor analysis was used to test the measurement model. Multiple group invariance analyses were also conducted to examine whether components of the measurement model were invariant across gender and ethnic groups (Malay and Chinese from Malaysia). Findings provide support for the reliability and factorial validity of the constructs. Results from the multi-group analyses suggest that all constructs are structured similarly across gender and ethnic groups.